Pengelolaan Sistem Informasi Reformasi Birokrasi Internal BBPPMPV BMTI Berbasis Content Management System Wordpress - Marsita Khusnul Khabibah; Cuhenda (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
Internal Bureaucracy Reform (RBI) serves as a strategic instrument for achieving transparent and accountable governance within government institutions. BBPPMPV BMTI currently faces significant challenges in disseminating information across eight reform areas due to conventional and fragmented data management. This research aims to design and develop an RBI Information System utilizing the WordPress Content Management System (CMS) to enhance document management efficiency and information accessibility. The system was developed using the Waterfall model, encompassing requirements analysis, UML-based design (Use Case, Sequence, and Activity Diagrams), implementation, and rigorous testing. The results demonstrate that the WordPress CMS enables dynamic and autonomous content management by administrators, eliminating the need for advanced programming expertise. Furthermore, integration with Google Drive cloud storage facilitates centralized, real-time report management. Functional verification via Black Box Testing confirms that the system achieved a 100% success rate across all test scenarios, proving it is valid and stable in meeting predefined specifications . In conclusion, this information system provides a structured and informative platform that accelerates bureaucratic reform at BBPPMPV BMTI through adaptive and cost-effective information technology.